Holding on to the past: Southern British evidence for mummification and retention of the dead in the Chalcolithic and Bronze Age. (December 2016) - Smith, Martin J.; Allen, Michael J.; Delbarre, Gabrielle; Booth, Thomas; Cheetham, Paul; Bailey, Lauren; O'Malley, Francine; Pearson, Mike Parker; Green, Martin
Abstract: Recent treatments of burial practices in prehistoric Europe have tended to emphasise the variety of practices that are apparent in any given period; contra previous views which tended to emphasise homogeneity over time. In the spirit of more recent considerations that emphasise a more holistic approach, the current article presents investigations of human remains interred within and around a single monument at Cranborne Chase, Dorset, UK. By taking a synthetic approach giving equal weight to taphonomy, archaeothanatology, histological analysis, scanning electron microscopy, micro-CT scanning, experimentation and contextual dating, a more nuanced picture has been revealed, where the dead were dealt with in ways that were both more complex and considerably more protracted than might otherwise be assumed. In particular, several lines of evidence point to practices aimed at the protracted curation of the dead as articulated bodies with at least some soft tissue persisting. This observation is of particular importance in light of previously published claims for 'mummification' in Bronze Age Britain. It suggests that such practices may have been both widespread and persistent over time. Highlights: A group of prehistoric burials from Britain show unexplained anomalies. We demonstrate these dead were retained for extended periods before burial. This suggests British 'mummification' was more widespread than previously realised.